(untitled) (ETIMA, 2024)
As a result of the control era of automotive technology which began in the late 20th century, IC engines contain a large number of sub-systems that allow for better engine performance and vehicle maneuverability, while at the same time they satisfy increasingly strict environmental norms and standards when it comes to exhaust emissions in what is known as an environmental-engineering compromise. However, tuning today’s high-performance engines in which the trade-offs between performance, economy and emissions take precedence is a challenge for even the most experienced automotive engineers as it includes major implications for the environmentalengineering compromise. The aim of this paper was to analyze these implications and determine if the changes in power and fuel consumption question the operation needs of the vehicle and the driver’s requirements, as well as the amount of exhaust emissions that find their way in the ambient air. The POWER/PERFORMANCE optimization led to a 36% increase in engine power (78 to 106 kW), a 9 % decrease in fuel consumption (6.6 to 6.0 l/100 km) and consequently 30% reduction in CO2 emissions (3.43 % to 2.38 % of the total volume of exhaust gasses). The ECONOMY optimization, which was primarily aimed at a decrease in fuel consumption and a climate-friendly improvement of the environmental map of the engine, led to a 42 % decrease in CO2 emissions (3.43 % to 1.99 % of the total volume of exhaust gasses) and a 13.5 % decrease in fuel consumption (6.6 to 5.7 l/100 km), while maintaining an increase in engine power for 23 % (78 to 96 kW). Aside from these obviously positive implications, the results provided an insight in the negative trade-offs that these optimizations bring, such as an increase in local pollutants, including PM and NOx emissions.